Conditions Related to the Nature of Hardship Necessitating Facilitation : A Comparative Study - Sarhan, Gufran; Ali, Hamid (Journal of Legal Sciences, 2023)
The implementation of the rule of hardship brings facilitation requires several conditions that must be observed in order for the provisions to turn from difficulty to ease for the taxpayer, whether those conditions are related to hardship necessitating facilitation or conditions related to the person charged with hardship. Knowing this issue is extremely important, especially with regard to hardships that were not mentioned in terms of control or specification.